Impact of tropical cyclone Tej on oceanic environment in the Arabian Peninsula - Chinta, Veeranjaneyulu; Kalhoro, Muhsan Ali; Tahir, Muhammad; Liang, Zhenlin; Song, Tony (Frontiers in Marine Science, 2025)
Tropical cyclones (TCs) significantly alter the upper oceanic environment through physical and biogeochemical processes. This study investigates the impact of category 3 TC Tej (20–25 October 2023) on oceanic conditions in the Arabian Peninsula, using satellite remote sensing and model-based ocean reanalysis products. Ocean changes were assessed during the cyclone active period (20–25 October 2023) to capture its immediate impact on the oceanic environment. The cyclone induced Sea Surface Temperature (SST) cooling of 2.5°C to 4.0°C, particularly within cyclonic eddies and along the right side of the storm track, with cooling effects penetrating the upper 100 meters due to wind-induced vertical mixing (mixed layer depth to 40-50) Ekman upwelling. Concurrently, Chlorophyll-a (Chl-a) concentrations increased up to 6 mg/m3, reflecting a fourfold rise driven by nutrient entrainment. Enhanced subsurface Chl-a was observed down to 50 meters. Sea Surface Height (SSH) dropped below 0.05 m in cyclonic eddies (12°N, 56°E) and rose above 0.8 m in anticyclonic eddies (15°N, 55°E), revealing contrasting vertical motions. Surface pH declined by 0.05-0.1 units, while dissolved inorganic carbon (DIC) concentrations increased to 2.1-2.2 mol/m3 in the upper 100 meters, attributed to enhanced CO2 uptake and the upwelling of CO2-rich waters. Cyclonic eddies were linked to lower SSH, higher Chl-a, and elevated DIC levels. This study provides the first high-resolution vertical analysis of post-Tej biogeochemical responses in the Arabian Peninsula, highlighting eddy-modulated nutrient redistribution as a key driver of phytoplankton bloom. These findings enhance understanding of the coupled physical-biogeochemical impacts of TCs in the region.